Urothelial Carcinoma in a 22-Year-Old Female with Angelman Syndrome. (11th April 2017) - Pugh, Jessica; Huffaker, R. Keith
Abstract : A 22-year-old nulligravid white female with Angelman syndrome was noted to have a 4-month history of premenstrual nausea, vomiting, and abdominal pain. She had an echogenic focus in her bladder noted on ultrasound. She was diagnosed with low grade urothelial carcinoma after cystoscopic evaluation with biopsy and was sent to urology for further treatment. Urothelial carcinoma is rare in individuals younger than age 40. Patients may present with gross hematuria. There is often a delay in diagnosis in younger individuals with different genetic mutations noted upon diagnosis.